Reiter syndrome accompanied by Terry nail - Coskun, BK; Saral, Y; Ozturk, P; Coskun, N (Wiley, 2005)
We present a case of Reiter syndrome (RS) associated with Terry nail in a 32-year-old male patient who also had subungual keratosis and onycholysis. The case had all the characteristic findings of complete RS including urethritis, conjunctivitis, arthritis and skin lesions, and based on these findings a clinical diagnosis was established. The patient complained of milky-white coloured leakage that was more frequent in the mornings, and dysuria. Urinary analysis revealed leucocytes and erythrocytes. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values were high. The case was considered as RS due to gonococcic urethritis. However, there was no growth in the culture. Self-report of the patient revealed that he had had continued symptoms and 9 months after the development of RS he developed Terry nail. To the best of our knowledge this is the first case of RS associated with Terry nail.
Keywords: onycholysis; Reiter syndrome; subungual keratosis; Terry nail